Effect of spindle speed during ultrasonic rolling on surface integrity and fatigue performance of Ti6Al4V alloy. (June 2022) - Pang, Zhiwei; Wang, Shuaixing; Yin, Xiaole; Yu, Shouming; Du, Nan
Graphical abstract: Highlights: Ultrasonic rolling processing refines the surface grains of Ti6Al4V alloy and forms compressive stress. Spindle speed strongly affects the surface integrity and plastic deformation degree. Ultrasonic rolling significantly improves the fatigue life of Ti6Al4V alloy. Spindle speed of 200 rpm can obtain the greatest gains to the fatigue resistance of Ti6Al4V alloy. Abstract: Ultrasonic rolling refines the surface grains of Ti6Al4V alloy and forms compressive stress. Spindle speed strongly affects the plastic deformation degree and then changes the surface roughness, microstructure and residual stress distribution. Compared with other spindle speeds, 200 rpm can obtain the lowest roughness of 0.049 μm, the deeper compressive stress field of ∼ 680 μm and greatest gains to the fatigue resistance of Ti6Al4V alloy. Excessive spindle speed will cause negative effects. High surface integrity, deep compressive stress field and surface nanocrystalline effect are considered to be important reasons for ultrasonic rolling to improve the fatigue performance of titanium alloy.